TI_GERICHTE 12.2004.10 vom 29. Dezember 2004 , cessione ex art. 260 LEF - legittimazione attiva - denominazione della parte attrice - TI Tribunale d'appello (2004)
cessione ex art. 260 LEF - legittimazione attiva - denominazione della parte attrice